2009
DOI: 10.1038/nature07684
|View full text |Cite
|
Sign up to set email alerts
|

Human occludin is a hepatitis C virus entry factor required for infection of mouse cells

Abstract: Hepatitis C virus (HCV) is a leading cause of liver disease worldwide. The development of much needed specific antiviral therapies and an effective vaccine has been hampered by the lack of a convenient small animal model. The determinants restricting HCV tropism to human and chimpanzee hosts are unknown. Replication of the viral RNA has been demonstrated in mouse cells1,2, but these cells are not infectable with either lentiviral particles bearing HCV glycoproteins (HCVpp)3 or HCV produced in cell culture (HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
849
1
14

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 827 publications
(890 citation statements)
references
References 19 publications
26
849
1
14
Order By: Relevance
“…6 Cell-surface factors essential for HCV entry, but not directly involved in lipid trafficking, include the tetraspanin, CD81, 7 and the tight-junction components, claudin-1 8 and occludin. 9 SR-BI is a 509-amino-acid protein with two transmembrane domains and a single large extracellular loop that is highly expressed in the liver and in tissues producing steroid hormones. 10 It is the key highdensity lipoprotein (HDL) receptor and mediates a flux of free cholesterol from the lipoprotein into the cellular membrane.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Cell-surface factors essential for HCV entry, but not directly involved in lipid trafficking, include the tetraspanin, CD81, 7 and the tight-junction components, claudin-1 8 and occludin. 9 SR-BI is a 509-amino-acid protein with two transmembrane domains and a single large extracellular loop that is highly expressed in the liver and in tissues producing steroid hormones. 10 It is the key highdensity lipoprotein (HDL) receptor and mediates a flux of free cholesterol from the lipoprotein into the cellular membrane.…”
mentioning
confidence: 99%
“…10,[12][13][14][15] First proposed as an HCV receptor because of its interaction with the viral glycoprotein, E2, 16 SR-BI was subsequently shown to be essential for HCV entry in numerous studies. 5,9,17,18 Animal data indicate that SR-BI is also important for HCV infection in vivo, 19 and an inhibitor of HCV/SR-BI interaction is the only HCVentry inhibitor currently in clinical trials. 20 Recent work has suggested that SR-BI fulfils at least two distinct functions during viral entry: one related to initial attachment and another during post-binding.…”
mentioning
confidence: 99%
“…Most recently, human occludin was identified as a crucial factor for HCV entry. 37 The involvement of these diverse molecules was first demonstrated using HCV pseudoparticles, but has now been verified in the infectious HCV cell culture system.…”
Section: Cell-based In Vitro Hcv Systemsmentioning
confidence: 99%
“…A better understanding of the essential host cell factors required for productive HCV infection by, for instance, genomewide RNA interference screening and microRNA profiling, may allow the manipulation of small laboratory animals as hosts of HCV infection. In this endeavor, the combined expression of human occludin and CD81, which makes mouse cells infectable by HCV, 37 and the expression of the liver-specific microRNA miR-122, which promotes viral replication in nonhepatocyte cells, 38 may hold promise for the future.…”
Section: Cell-based In Vitro Hcv Systemsmentioning
confidence: 99%
See 1 more Smart Citation